Alamethicin for using in bioavailability studies? – Re-evaluation of its effect. (March 2017) - Vollmer, Maren; Klingebiel, Mirko; Rohn, Sascha; Maul, Ronald
Abstract: A major pathway for the elimination of drugs is the biliary and renal excretion following the formation of more hydrophilic secondary metabolites such as glucuronides. For in vitro investigations of the phase II metabolism, hepatic microsomes are commonly used in the combination with the pore-forming peptide alamethicin, also to give estimates for the in vivo situation. Thus, alamethicin may represent a neglected parameter in the characterization of microsomal in vitro assays. In the present study, the influence of varying alamethicin concentrations on glucuronide formation of selected phenolic compounds was investigated systematically. A correlation between the alamethicin impact and the lipophilicity of the investigated substrates was analyzed as well. Lipophilicity was determined by the logarithm of the octanol-water partition coefficient. For every substrate, a distinct alamethicin concentration could be detected leading to a maximal glucuronidation activity. Further increase of the alamethicin application led to negative effects. The differences between the maximum depletion rates with and without alamethicin addition varied between 2.7% and 18.2% depending on the substrate. A dependence on the lipophilicity could not be confirmed. Calculation of the apparent intrinsic clearance led to a more than 2-fold increase using the most effective alamethicin concentration compared to the alamethicin free control. Highlights: Alamethicin affects glucuronidation of phenolic substrates. Different alamethicin concentrations lead to different depletion rates. A maximal glucuronidation activity could be assigned to different but distinct alamethicin concentrations. Alamethicin application is a crucial factor to deduce enzyme kinetic parameter from in vitro metabolic assays. Correlations between the substrate lipophilicity and alamethicin effect were not detected.